Cameroon's Schools: Sites of Sexual, Physical, and Psychological Violence Against Girls. Issue 1 (1st March 2023) - Moundene, Linda Silim
Abstract: In this article, the data for which I acquired through a systematic review of articles published over three years, focusing on analyzing the evolution of the situation over these past years, I discuss school-based gender violence in Cameroon. Considering the complexity of Cameroonian society and its responses to violence against girls and women, we need to establish that violence can be addressed, and we have to suggest how this can be done. From one region to another, a girl being denied access to education, being trafficked, or being forced into early marriage constitutes an experience of violence. Even though the government has been fighting these ills for the past twenty years the results show that girls are still highly vulnerable in the education system.